STRATEGI PROMOSI MEDICAL CHECK-UP COVID-19 RSUD MATRAMAN - Gustik, Vellyana; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
The community's need for health services during the Coronavirus Disease (COVID-19) pandemic has increased drastically. The need for health services at the hospital level includes examining and issuing a COVID-19 examination certificate. Responding to this, the Matraman Hospital incidentally created a new service, the COVID-19 Medical Check-Up (MCU). The management of RSUD Matraman realizes the importance of a promotional strategy to increase public interest in using the new service. This study aims to obtain an overview of the MCU COVID-19 service promotion strategy at the Matraman Hospital. The case study design in this study uses qualitative methods with in-depth interviews with informants. The results of this study, RSUD Matraman implemented four promotional strategies; (1) Advertising for disseminating information through social media, Instagram, (2) Sales Promotion by making leaflets, standing banners, and short videos that can make it easier for consumers to see service information. (3) Personal Selling by providing customer satisfaction surveys to MCU patients to get an overview of service quality and (4) publicity from wider stakeholders such as Dinas Kesehatan Provinsi DKI Jakarta. These four promotion strategies complement each other in disseminating service information and effectively increasing interest in patient visits at RSUD Matraman. It is necessary to monitor and evaluate the promotion strategy for the MCU COVID-19 service carried out by RSUD Matraman to get an overview of the most effective and efficient promotion strategy steps.